Carposina sasakii (Lepidoptera: Carposinidae) in its Native Range Consists of Two Sympatric Cryptic Lineages as Revealed by Mitochondrial COI Gene Sequences. Issue 1 (1st July 2015) - Wang, J.; Yu, Y.; Li, L.-L.; Guo, D.; Tao, Y.-L.; Chu, D.
Abstract : The genetic differentiation and genetic structure of the peach fruit moth, Carposina sasakii Matsumura (Lepidoptera: Carposinidae), was investigated in China, where the moth is native. The mitochondrial cytochrome c oxidase I ( COI ) gene of 180 individuals from 16 collections were sequenced and analyzed. The results showed that two sympatric and cryptic mtDNA lineages existed within C. sasakii in China. The genetic differentiation has significant correlation with the geographical distance, but has no evidence for host plant associations. Our results of haplotype distribution suggest that the C. sasakii individuals can naturally move between areas, while the movement of individuals between long-distance locations may be associated with human activities such as the transport of fruit. Finally, an mitochondrial COI gene PCR-RFLP method was developed to differentiate the two cryptic mtDNA lineages within C. sasakii, which provides rapid and reliable tool for the future research of the two lineages.